Microscopic model of carbonaceous nanoporous molecular sieves—anomalous transport in molecularly confined spaces - Kowalczyk, Poitr; Gauden, P.; Terzyk, A.; Furmaniak, S. (Royal Society of Chemistry, 2010)
To model the equilibrium and transport properties of carbonaceous molecular sieves (CMS)(i.e., carbon membranes, coals, activated carbons with ink-bottle pore geometry, etc.) the newmicroscopic turbostratic carbon pore model (TCPM) is developed. Analysis of experimentalGibbs excess of methane adsorption on Shirasagi CMS 3K-161 at 298 K indicates thatinvestigated CMS is structurally a heterogonous material (i.e., it is composed of slit-shaped andturbostratic carbon nanopores of different sizes). The predicted absolute methane isotherm,total pore volume of 0.22 cm3 g1, enthalpy of methane adsorption of 17.5–18.6 kJ mol1 onShirasagi CMS 3K-161 at 298 K are in good agreement with existing experimental and theoreticaldata. Applying TCPM, we model the equilibrium and kinetic separation of hydrogen andmethane mixtures adsorbed in CMS turbostratic carbon nanopores at infinite dilution and194.7, 293.2, 313.2, 423.2, and 573.2 K. We found that near ambient temperatures one canreach equilibrium selectivity of methane over hydrogen (CH4/H2) of 102 in the turbostraticcarbon nanopores having effective cage sizes of E5 A° . Lowering an operating temperature downto the dry ice one increases the equilibrium CH4/H2 selectivity in these nanopores up to 103.The kinetic selectivity of hydrogen over several investigated fluids, including: methane, argon,xenon, nitrogen, and carbon dioxide at studied operating conditions does not depend on the sizeof the carbon nanopore cage. This simply means that the kinetic separation factor is controlledby the size of the carbon nanopore constriction. Taking this into account, we predicted theeffective size of the carbon nanopore constriction of real CMS from the experimentallymeasured kinetic H2/CH4 selectivities at infinite dilution. The high kinetic H2/CH4 selectivity of102–103 corresponds to the effective size of the carbon nanopore constriction of r2.958 A °(i.e., lower or equal to the collision diameter of hydrogen molecule). However, decreasing/increasing of the effective size of the carbon nanopore constriction by E0.1–0.2 A °exponentially increases/decreases kinetic H2/CH4 separation factor. Finally, we showedthat the efficiency of kinetic separation at 298 K and infinite dilution depends on the sH2/sXand not only on sH2(where s denotes the collision diameter of hydrogen and the mentionedabove fluids, respectively).